THE EFFECTIVENESS OF GUTINMATHE'S IN BLOG-BASED LEARNING WITH A CONTEXTUAL APPROACH ON LINEAR EQUATION SYSTEM - Siti Inganah; Lilik Mahmulah; Adi Slamet Kusumawardana (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
This study aimed to determine how effective the learning is using Gutinmathe's blog with a contextual approach. This research employed a quantitative approach and ADDIE Web development method, with analysis, design, development, implementation, and evaluation stages. The population in this study were Year 10 students of one of the vocational high School in Pandaan, Indonesia and the samples were Year 10 students majoring in Medical Laboratory Technology from the school. The data was analyzed using the paired-sample t-test conducted by SPSS. Gutinmathe's blog learning media was validated by two media expert lecturers and one teacher. The media validation score was 78.33%, meaning that the blog media is feasible to use. The results of this study indicate differences in learning outcomes before and after using the Gutinmathe blog-based learning media, where the students' post-test answers are better than the pre-test. It shows that using Gutinmathe's blog-based learning media with a contextual approach is effective.